Brain Microbiota in Huntington’s Disease Patients - Alonso, Ruth; Pisa, Diana; Carrasco, Luis (Frontiers in Microbiology, 2019)
One of the most important challenges facing medical science is to better understand the cause of neuronal pathology in neurodegenerative diseases. Such is the case for Huntington’s disease (HD), a genetic disorder primarily caused by a triplet expansion in the Huntingtin gene (HTT). Although aberrant HTT is expressed from embryogenesis, it remains puzzling as to why the onset of disease symptoms manifest only after several decades of life. In the present study, we investigated the possibility of microbial infection in brain tissue from patients with HD, reasoning that perhaps mutated HTT could be deleterious for immune cells and neural tissue, and could facilitate microbial colonization. Using immunohistochemistry approaches, we observed a variety of fungal structures in the striatum and frontal cortex of seven HD patients. Some of these fungi were found in close proximity to the nucleus, or even as intranuclear inclusions. Identification of the fungal species was accomplished by next generation sequencing (NGS). Interestingly, some genera, such as Ramularia, appeared unique to HD patients, and have not been previously described in other neurodegenerative diseases. Several bacterial species were also identified both by PCR and NGS. Notably, a curved and filamentous structure that immunoreacts with anti-bacterial antibodies was characteristic of HD brains and has not been previously observed in brain tissue from neurodegenerative patients. Prevalent bacterial genera included Pseudomonas, Acinetobacter and Burkholderia. Collectively, our results represent the first attempt to identify the brain microbiota in HD. Our observations suggest that microbial colonization may be a risk factor for HD and might explain why the onset of the disease appears after several decades of life. Importantly, they may open a new field of investigation and could help in the design of new therapeutic strategies for this devastating disorder.